Menopausal‭ Transition Raises Vulnerability for Anxiety and Depression Disorders‬‬‬ - Parikh MD, Dr‭ Parinda; Gellert, Zoe; Shukla MD, Dr Arnesh; Manepalli, Sahia; Pansuriya‭ MD, Dr Parthiv‬; Singh MD, Dr Shaurya Kumar; Suthar MD, Dr‬ Himani J; Buddhavarapu, Mahiya; Wang, Eric; Chandra, Arushi Kaushik; et al. (International Journal of Innovative Research in Medical Science, 2025)
Background & Objective: Hormonal instability during the menopausal transition negatively impacts the limbic and prefrontal circuits, heightening women’s vulnerability to depressive disorders and anxiety. This narrative review integrates basic-science and clinical evidence to clarify how perimenopausal endocrine disturbances increase vulnerability to depression and anxiety, and whether augmenting first-line antidepressants with hormone replacement therapy (HRT) offers superior relief. Methods: English-language literature between the years 1990 – 2024 was searched in PubMed and Google Scholar for studies on menopause, estradiol, depression, anxiety, selective-serotonin/-norepinephrine reuptake inhibitors (SSRI/SNRI), and HRT. Preference was given to randomised controlled trials (RCTs), meta-analyses, and extensive cohort studies; mechanistic papers were included when they provided insight into pathophysiology. Findings were collated qualitatively. Results & Conclusion: Estrogen withdrawal disrupts serotonergic concentration, upregulates HPA-axis reactivity, and alters ERα/ERβ signalling in limbic-cortical circuits, predisposing to mood lability, especially in late perimenopause. Multiple studies and a 2023 network meta-analysis demonstrate that adding systemic estradiol (with or without progesterone) to fluoxetine or similar agents yields higher response and symptomatic remission rates (up to 92% vs. 48%) than either modality alone. However, systemic HRT also raises breast cancer, thromboembolic, and stroke risk, with the magnitude increasing over prolonged use.